Research on Sleep (IntechOpen, 2025)
Why publish a new book on sleep? The reasons are compelling. There is a growing recognition in clinical practice of our limited understanding of sleep, alongside a constant stream of discoveries and insights into this fundamental homeostatic process of our lives. Sleep is a universal experience; everyone has something to say about it, as it envelops us from the very start of our existence. Each night brings a transformation, making sleep a uniquely different experience, even for the same individual. From adolescence to old age, sleep evolves, shifting through the stages of menopause and becoming altered during various health conditions like cardiovascular diseases, OSAS, and particularly epilepsy. This new text aspires to offer the latest updates on key themes related to sleep, striving to inspire clinicians and researchers alike to explore new ideas and perspectives.